2005
DOI: 10.1111/j.1600-0838.2005.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability and prediction of physical activity in 5‐, 10‐, and 28‐year follow‐up studies among industrial employees

Abstract: The aim of the study was to examine the stability of voluntary and household physical activity (PA) and to compare it with that of the use of the most common stimulants. The prospective cohort study comprised of follow-ups at 5, 10, and 28 years at baseline in 1973 in four plants of an industrial corporation in Finland. A systematic, non-proportional sample (n=902, age range 18-64 years) stratified for age, gender, and occupational status was drawn from the employees. Scores of PA were based on a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
3
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 23 publications
3
27
3
3
Order By: Relevance
“…Although, among men, the results of the unadjusted model for the age category 12-19 years ported have been only low or moderate 5) . In another study, the correlation between the time points studied was found to weaken over time 13) . Only a few studies have examined whether physical activity in early life tracks to an older age.…”
Section: Discussionmentioning
confidence: 90%
“…Although, among men, the results of the unadjusted model for the age category 12-19 years ported have been only low or moderate 5) . In another study, the correlation between the time points studied was found to weaken over time 13) . Only a few studies have examined whether physical activity in early life tracks to an older age.…”
Section: Discussionmentioning
confidence: 90%
“…The correlations for comparable age groups in a Finnish study over 9 years were 0.61 for male and 0.31 for female participants from age 18 to 27 and 0.58 and 0.51 from age 21 to 30, respectively [27]. In another Finnish study, stability over 5 years in 18-to 64-year-olds was 0.46 and 0.34 for male and for female subjects, and stability over 10 years was 0.25 and 0.29, respectively [28]. The 4-year tracking correlation in an American study from age 25 to 29 was 0.21 for both sexes [29], and another American study showed a correlation of 0.30 in a follow-up of female participants from age 31 to 38 [30].…”
Section: Tracking Of Physical Activity In Adulthoodmentioning
confidence: 95%
“…The two methods gave highly similar results [8]. All subjects at baseline underwent the assessment of LTPA.…”
Section: Methodsmentioning
confidence: 62%
“…It was, however, an indirect measurement based on self-report and thus subject to recall bias. Strenuous LTPA tracked rather well in follow-ups of the sample [8]. Regardless of the rather small study sample a clear inverse association between strenuous LTPA and backrelated hospitalizations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation